The main integrative discipline as manager of the formation of the modes of action of the future professional education - Leticia Guillot-Mustelier; Aida María Ocejo-Salvador; Sergio Repilado-Santa Cruz Pacheco (Maestro y Sociedad, 2017)
For the formation of the professional future that is carried out from the Cuban University, it is identified to the Integrative Main Discipline, as the spine of the formation process which responds to the logic of the profession, and he/she leans on in the contributions of the remaining disciplines of the career assuming them in their integration to assure the domain in the ways of that professional's performance. It is for that reason that to guarantee their appropriate design, as well as the preparation of the cloister for its deliberate and coherent work, so that the traffic in the students' growing way is achieved by the necessary actions for the development in the way of performance of the professional future, he/she becomes one of the challenges foreseen from the educational strategies of the careers and years.